Unraveling the Genetic Basis of Key Agronomic Traits of Wrinkled Vining Pea (Pisum sativum L.) for Sustainable Production - Alemu, Admas; Brantestam, Agnese Kolodinska; Chawade, Aakash (Frontiers in Plant Science, 2022)
Estimating the allelic variation and exploring the genetic basis of quantitatively inherited complex traits are the two foremost breeding scenarios for sustainable crop production. The current study utilized 188 wrinkled vining pea genotypes comprising historical varieties and breeding lines to evaluate the existing genetic diversity and detect molecular markers associated with traits relevant to vining pea production such as green pea yield (YTM100), plant height (PH), earliness (ERL), adult plant resistance to downy mildew (DM), pod length (PDL), numbers of pods per plant (PDP), number of peas per pod (PPD) and proportion of small green peas (PSP). Marker-trait associations (MTAs) were conducted using 6902 quality SNP (Single nucleotide polymorphism) markers generated from the DArTseq and GBS sequencing methods. The best linear unbiased prediction (BLUP) values were estimated from the two-decades-long (1999-2020) unbalanced phenotypic data sets recorded from two private breeding programs, Findus and Birds eye, now owned by Nomad Foods. Analysis of variance revealed a highly significant variation between genotypes and genotype-by-environment interactions for the ten traits. The genetic diversity and population structure analysis estimated an intermediate level of genetic variation with two optimal sub-groups within the current panel. A total of 48 significant (P < 0.0001) MTAs were identified for eight different traits, including five for green pea yield on chr2LG1, chr4LG4, chr7LG7 and scaffolds (two) and six for adult plant resistance to downy on chr1LG6, chr3LG5 (two), chr6LG2 and chr7LG7 (two). We reported several novel MTAs for different crucial traits with agronomic importance in vining pea production for the first time and these candidate markers could be easily validated and integrated into the active breeding programs for marker-assisted selection.